HOT DENSE MAGNETIZED SPINOR MATTER IN PARTICLE AND ASTROPARICLE PHYSICS: THE ROLE OF BOUNDARIES - Sitenko, Yu. A. (Одеські астрономічні публікації, 2016)
We study the influence of boundaries on chiral effects in hot dense relativistic spinor matter in a strong magnetic field which is orthogonal to the boundaries. The most general set of boundary conditions ensuring the confinement of matter within the boundaries is employed. We find that the chiral magnetic effect disappears, whereas the chiral separation effect stays on, becoming dependent on temperature and on a choice of boundary conditions. As temperature increases from zero to large values, a stepped-shape behaviour of the chiral separation effect as a function of chemical potential is changed to a smooth one. A choice of the boundary condition can facilitate either amplification or diminution of the chiral separation effect; in particular, the effect can persist even at zero chemical potential, if temperature is finite. This points at a significant role of boundaries for physical systems with hot dense magnetized spinor matter, i.e. compact astrophysical objects (neutron stars and magnetars), relativistic heavy-ion collisions, novel materials known as the Dirac and Weyl semimetals.